Tetramer‐based identification of naïve antigen‐specific B cells within a polyclonal repertoire. Issue 7 (17th April 2018) - Brooks, Jeremy F.; Liu, Xiao; Davies, Janet M.; Wells, James W.; Steptoe, Raymond J.
Abstract : Detecting naïve antigen‐specific B cells can be challenging. Use of multiple, complementary tetramers with different fluorochromes enhances sensitivity and specificity allowing naïve antigen‐specific B cells to be readily distinguished within a polyclonal repertoire. Activated, affinity‐matured B cells, however, can be detected effectively using a single tetramer.